2014
DOI: 10.1111/jam.12558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosecond pulsed electric field on Escherichia coli in water: inactivation and impact on protein changes

Abstract: Aims: This article shows the effect of nanosecond pulsed electric field (nsPEF) on Escherichia coli, which could imply a durable change in protein expressions and then impacted the phenotype of surviving bacteria that might lead to increase pathogenicity. Methods and Results: The effects of nsPEF on E. coli viability and membrane permeabilization were investigated. One log 10 reduction in bacterial counts was achieved at field strength of 10 7 V m À1 with a train of 500 successive pulses of 60 9 10 À9 s. Incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…In the present study we show in vitro results for the efficacy of 600-ns PEF to inactivate Escherichia coli and Lactobacillus acidophilus. While the effects of nsPEF have been studied on E. coli (Chalise et al 2006;Perni et al 2007;Guionet et al 2014Guionet et al , 2015Novickij et al 2018) and other species such as Staphylococcus aureus (Chaturongakul and Kirawanich 2012; Vadlamani et al 2018;Novickij et al 2019), Salmonella typhimurium (Perni et al 2007) and Bacillus subtilis (Katsuki et al 2002); we chose to compare the effects of E. coli with L. acidophilus for two reasons. First, several studies have suggested that cell size and shape play a critical role in transmembrane potential charging and subsequent membrane pore formation (Kandušer and Miklavčič 2008;Khan and El-Hag 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we show in vitro results for the efficacy of 600-ns PEF to inactivate Escherichia coli and Lactobacillus acidophilus. While the effects of nsPEF have been studied on E. coli (Chalise et al 2006;Perni et al 2007;Guionet et al 2014Guionet et al , 2015Novickij et al 2018) and other species such as Staphylococcus aureus (Chaturongakul and Kirawanich 2012; Vadlamani et al 2018;Novickij et al 2019), Salmonella typhimurium (Perni et al 2007) and Bacillus subtilis (Katsuki et al 2002); we chose to compare the effects of E. coli with L. acidophilus for two reasons. First, several studies have suggested that cell size and shape play a critical role in transmembrane potential charging and subsequent membrane pore formation (Kandušer and Miklavčič 2008;Khan and El-Hag 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While some cell lines, e.g., U937 and Jurkat cells 52 , show signifi cant changes, others do not react in the same way. Studies involving E. coli did not show signifi cant changes in protein pattern 53 .…”
Section: Change In Protein Pattern Of Cellsmentioning
confidence: 94%
“…For instance, the development of generators with more potent electrical fields operating with pulse widths in the nanosecond region are necessary. These new generators have to operate in accordance with reduced energy demand, have minimal heating effect, and spark generation between the electrodes …”
Section: Pef Equipment and Designmentioning
confidence: 99%
“…This condition can be achieved by applying high‐intensity electric pulses (varying between 15 and 60 kV cm −1 among different microorganisms) for short periods (a few microseconds) in the food matrix . Moreover, the effect of PEF treatment varies among microorganisms and between vegetative and spore forms …”
Section: Effect Of Pef With Mild Heating On Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation